De novo assembly and transcriptome analysis of two contrary tillering mutants to learn the mechanisms of tillers outgrowth in switchgrass (Panicum virgatum L.) - Xu, Kaijie; Sun, Fengli; Wang, Yongfeng Wang; Chai, Guaiqiang; Shi, Lili; Liu, Shudong; Xi, Yajun (Frontiers in Plant Science, 2015)
Tillering is an important trait in monocotyledon plants. The switchgrass (Panicum virgatum), studied usually as a source of biomass for energy production, can produce hundreds of tillers in its lifetime. Studying the tillering of switchgrass also provides information for other monocot crops. High-tillering and low-tillering mutants were produced by ethyl methanesulfonate (EMS) mutagenesis. Alteration of tillering ability resulted from different tiller buds outgrowth in the two mutants. We sequenced the tiller buds transcriptomes of high-tillering and low-tillering plants using next-generation sequencing technology, and generated 34 G data in total. In the de novo assembly results, 133,828 unigenes were detected with an average length of 1,238 bp, and 5,290 unigenes were differentially expressed between the two mutants, including 3,225 up-regulated genes and 2,065 down-regulated genes. Differentially expressed gene (DEG) analysis with functional annotations was performed to identify candidate genes involved in tiller bud outgrowth processes using Gene Ontology (GO) classification, Cluster of Orthologous Groups of proteins (COG), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. This is the first study to explore the tillering transcriptome in two types of tillering mutants by de novo sequencing.